Burnout: Manifestation of Work Engagement and Avoidance Coping Among Nurses - Fayza Aliyya Ramadhani; Dewi Khrisna Sawitri (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2026)
Purpose – This study analyzes the relationship between work engagement, avoidance coping, and burnout among nurses. It specifically investigates the mediating role of avoidance coping in the pathway from positive work engagement to reduced burnout. Design/methodology/approach – A quantitative, explanatory cross-sectional design was used. Data were collected via questionnaires from 59 inpatient nurses at a private hospital in Surabaya and analyzed using the PLS-SEM method. Originality – This study clarifies the specific behavioural mechanism (avoidance coping) through which a positive psychological state protects nurses. This confirms that engagement prevents burnout through a dual pathway: directly, and indirectly by reducing the adoption of maladaptive coping strategies. Findings and Discussion – The results show that work engagement significantly and negatively predicts both burnout and the use of avoidance coping. Avoidance coping, in turn, was a significant positive predictor of burnout. The key finding is that avoidance coping significantly mediates the relationship between work engagement and burnout. This implies that engagement's protective effect is not just psychological but also behavioral. Conclusion – Work engagement prevents burnout through a dual pathway: it acts as a direct psychological shield and, indirectly, it reduces the adoption of maladaptive coping strategies.